How a neutral evolutionary ratchet can build cellular complexity - Lukeš, Julius; Archibald, John M; Keeling, Patrick J; Doolittle, W. Ford; Gray, Michael W (IUBMB life, 2011)
Complex cellular machines and processes are commonly believed to be products of selection, and it is typically understood to be the job of evolutionary biologists to show how selective advantage can account for each step in their origin and subsequent growth in complexity. Here, we describe how complex machines might instead evolve in the absence of positive selection through a process of "presuppression," first termed constructive neutral evolution (CNE) more than a decade ago. If an autonomously functioning cellular component acquires mutations that make it dependent for function on another, pre-existing component or process, and if there are multiple ways in which such dependence may arise, then dependence inevitably will arise and reversal to independence is unlikely. Thus, CNE is a unidirectional evolutionary ratchet leading to complexity, if complexity is equated with the number of components or steps necessary to carry out a cellular process. CNE can explain "functions" that seem to make little sense in terms of cellular economy, like RNA editing or splicing, but it may also contribute to the complexity of machines with clear benefit to the cell, like the ribosome, and to organismal complexity overall. We suggest that CNE-based evolutionary scenarios are in these and other cases less forced than the selectionist or adaptationist narratives that are generally told.
Keywords: modely genetické; rostliny; Animals; Plants; genetický drift; Humans; lidé; Models, Genetic; zvířata; biologická evoluce; Biological Evolution; sestřih RNA; Genetic Drift; RNA Editing; fyziologická adaptace; RNA Splicing; editace RNA; Adaptation, Physiological